PENGARUH MOTIVASI KERJA, SUPERVISI KLINIS DAN SARANA PRASARANATERHADAP KINERJA GURU PADA SMA NEGERI DI KECAMATAN NUSANIWE KOTA AMBON (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research aims are (1) to describe whether there is work motivation influence, clinical supervision and the facility infrastructure toward teachers’ performance. (2) to describe whether there is work motivation influence toward teachers’ performance. (3) to describe whether there is clinical supervision influenceof toward teachers’ performance. (4) to describe whether there is facility infrastructure effect toward teacher performance.This research was conducted at three public senior high school (SMAN) in Nusaniwe District of Ambon City, the civil servant teachers as a population of 150 teachers. The sample of 150 teachers with taken by sampling technique of this research is saturated sampling.Research results show that: (1) there is positive and significant influence on work motivation, clinical supervision and facility infrastructure on teacher’s performance simultaneosly. Work motivation gives its significant contribution to the teacher’s performance the contribution is 5,2%, the contribution of facility infrastructure of 14.81% and the contribution of clinical supervision is 14,11%. (2) there is positive and significant influence between work motivation toward teachers’ performance. (3) there is positive and significant influence between clinical supervision toward teacher’s performance, (4) there is positive and significant influence between facility infrastructure toward teacher’s performance.